Tinjauan Variasi Produk Vitamin Blackmores Di PT. Enseval Putera Megatrading Bogor - Zahdi, Fahmi Ramadhan; Suardy, Weman (Jurnal Aplikasi Bisnis Kesatuan, 2024)
Vitamin products have become a necessity for society, because people gain many benefits by consuming vitamin products according to their individual needs. PT. Enseval Putera Megatrading Tbk is a company that operates in the distribution and logistics sector through the provision of health products. The aim of the research is to find out; 1. To find out what variations of Blackmores products are available at PT. Enseval Putera Megatrading; 2. To find out what the obstacles are to blackmores product variations at PT. Enseval Putera Megatrading; 3. to find out how to deal with obstacles to Balckmores product variations at PT. Enseval Putera Megatrading. The Research result; 1. PT. Enseval Putera Megatrading applies product variation measures, namely width, length, depth, consistency; 2. several obstacles; when there is a resizing of product variations from the initial product to smaller contents, customers prefer the more economical ones so that the initial product becomes slow moving; 3. In an effort to overcome the problem of slow moving initial products, the company provides bonus prizes so that customers are more interested in purchasing initial products that contain more content.   Keywords: Product Variations, Blackmores Vitamins